RP HPLC Method Development and Validation for Estimation of Orlistat in Pharmaceutical Dosage Forms: Pharmaceutical Science-Pharmaceutical analysis - Vivekanandan, V.; Kumudha, D. (International Journal of Life Science and Pharma Research, 2022)
Orlistat is an anti-obesity drug that inhibits the secretion of gastric and pancreatic lipases. Normally lipase breakdown triglyceride in the intestine as a result of metabolism. Despite the numerous advantages of this drug, researchers are facing problems with estimation by HPLC because limited methods are available; only United State Pharmacopoeia (USP) method is most reliable and effective. The present work aimed to develop an RP- HPLC method for determining orlistat in floating microcapsules. Considering the virtual reality in drug testing, quality control of dosage forms is the main criterion to be followed in the Pharmaceutical industry, which is to establish the procedures undertaken to ensure the identity and purity of a particular dosage form. Syncronis C18, 150mm x 4.6mm, 3μm column were used. Isocratic elution was performed with ACN:Water mixture. The flow rate was 2.0 mL min-1 and UV detection was at 205 nm. Caffeine was used as an internal standard. The developed method was validated according to the ICH guidelines and found to be linear within the range 150-600 ppm of Orlistat. In addition, this method was validated for its suitability, accuracy, precision, selectivity, robustness, and ruggedness per the ICH guidelines. The results HPLC analytical method validation was suitable for the quantitative and qualitative analysis of orlistat and it showed that this method could be successfully utilized for the identification and quantification of orlistat in any dosage form, with high resolution, accuracy, and precision.